The Effectiveness Of Spraying Nano Bone Ash And Oil Palm Emty Fruit Bunch Ash On Leaf Character Appearance Of Rice Mandel Variety - Hariyono, Hariyono; Isnawan, Bambang (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2023)
.         This study aims to determine the effectiveness of spraying nano  bone ash and palm oil emty   fruit  bunnch ash on  leaf  character appearance of rice Mandel variety. This research was carried out in the Agricultural Experiment Grenn House of the Muhammadiyah University of Yogyakarta in January to June2021. This study uses a single factor design arranged in a Complete Randomized Design (CRD), there are 4 treatm  ents. Each tratments consisted  of 6 plant samples with 3 replications namely: P. Urea 250 kg/hectare + SP-36 100 kg/hectare + KCl 100 kg/hectare, Q.Urea 250 kg/hectare + SP-36 50 kg/hectare + KCl 100 kg/hectare + Nano Bone Ash  concentration 0,2 %, R. Urea 250 kg/hectare + SP-36 100 kg/hectare + KCl 50 kg/hectare + Nano OPEFB Ash concentration 0,3 %, S.Urea 250 kg/hectare + SP-36 50 kg/hectare + KCl 50 kg/hectare + Nano Bone Ash concentration 0,2 % and Nano OPEFB  Ash concentration 0,3 %.  The results showed that the application of Urea 250 kg/hectare + SP-36 50 kg/hectare + KCl 50 kg/hectare + 0.2% Nano Bone Ash Concentration and 0.3% OPEFB Nano Ash concentration gave a significant effect on the character.sheat of leaf color, blade of leaf, chlorophyll content, length and width of stomata.